Roof watching - Jupp, Edmund W. (--Watching., 2002)
The aim of the Watching series is to draw attention to some of the very interesting items around us, things that perhaps we don't notice as much as we might. The first was Bridge Watching, and when this was put "on the Net" it produced, to the surprise of the author, such a pleasant flood of e-mail that another was written, called Water Watching. This, too, was kindly received. So it was tempting to continue with the theme. Roof Watching is an invitation to look at the top covering of buildings! Our eyes are set in our faces so that they look horizontally. Hence, in the ordinary way, people mostly look straight ahead, and don't look up as much as they might. If they did this too much they might not see objects at ground level, and so bump into things, of course; on the other hand, there is a good deal above eye level that is worth seeing. It is not only the outside of a roof that is of interest. Inside they're all sorts of intriguing things. If you hadn't thought much about it before, you may be surprised at what goes on inside the roof space, and what holds it all up. So, inside and outside, the roof is worth some attention, not only when complete, but during its construction, too. A building site can be worth a visit at any stage of the construction. It is particularly so when the roof is being built. The variety of shapes, textures, and colours of the covering provides a fascinating display to delight the eye and enchant the enquiring mind. Knowing something of the "why" and the "how" can add much to the absorbing pastime of just looking at roofs